Cold Agglutinins and Cryoglobulins Associate With Clinical and Laboratory Parameters of Cold Urticaria - Bizjak, Mojca; Košnik, Mitja; Terhorst-Molawi, Dorothea; Dinevski, Dejan; Maurer, Marcus (Frontiers in Immunology, 2021)
Mast cell-activating signals in cold urticaria are not yet well defined and are likely to be heterogeneous. Cold agglutinins and cryoglobulins have been described as factors possibly associated with cold urticaria, but their relevance has not been explained. We performed a single-center prospective cohort study of 35 cold urticaria patients. Cold agglutinin and cryoglobulin test results, demographics, detailed history data, cold stimulation test results, complete blood count values, C-reactive protein, total immunoglobulin E levels, and basal serum tryptase levels were analyzed. Forty six percent (n = 16) of 35 tested patients had a positive cold agglutinin test and 27% (n = 9) of 33 tested patients had a positive cryoglobulin test. Cold agglutinin positive patients, when compared to cold agglutinin negative ones, were mainly female (P = 0.030). No gender-association was found for cryoglobulins. A positive cold agglutinin test, but not a positive cryoglobulin test, was associated with a higher rate of reactions triggered by cold ambient air (P = 0.009) or immersion in cold water (P = 0.041), and aggravated by increased summer humidity (P = 0.007). Additionally, patients with a positive cold agglutinin test had a higher frequency of angioedema triggered by ingestion of cold foods or drinks (P = 0.043), and lower disease control based on Urticaria Control Test (P = 0.023). Cold agglutinin levels correlated with erythrocyte counts (r = −0.372, P = 0.028) and monocyte counts (r = −0.425, P = 0.011). Cryoglobulin concentrations correlated with basal serum tryptase levels (r = 0.733, P = 0.025) and cold urticaria duration (r = 0.683, P = 0.042). Results of our study suggest that cold agglutinins and cryoglobulins, in a subpopulation of cold urticaria patients, are linked to the course and possibly the pathogenesis of their disease.